State of Lake Superior - Munawar, M.; Munawar, I. F. (Ecovision world monograph series., 2009)
Lake Superior was saved from the extremes felt elsewhere because it is the top of the drainage landscape. Superior offered the prospects of greatest success because it was, in general, least altered. Many decades later, Superior serves as the best example of success in recovering from environmental adversity. This is not to say that restoration is complete or that all ecological problems are resolved. The heavy hand of humanity continues to cause important threats to the present and future state of Lake Superior. State of Lake Superior offers a polythetic view of current conditions in Lake Superior and insightful suggestions about where and how improvements should continue. The chapters range from basic reviews of what we know as a consequence of effective research to explorations of what little we know about challenging environmental issues for the future. Among these are the continuing concerns about contaminants, the burgeoning march of invasive species, and the portent of global change. We find some encouragement in the resilience of this large lake ecosystem. In many respects, it is a success story, as is shown from the insights of research merged with the mindful attention of management agencies.